Shifting the focus: energy demand in a net-zero carbon UK - Fawcett, T; Webb, J; Reiss, S; Hawkey, D; Mallaburn, P (Centre for Research into Energy Demand Solutions, 2019)
Our report takes the Government’s most recent statement on energy transition, the Clean Growth Strategy (BEIS, 2017), as a starting point and draws on current knowledge from the UK energy demand research community.